Cafeteria system: using captcha authentication and SHA-256 encryption - Bhaarudin, Muhammad Hafizhullah; Mohd Supir, Mohd Hafifi (College of Computing, Informatics, and Mathematics, 2025)
The cafeteria system at UiTM Melaka Jasin Campus was developed to improve the efficiency of food ordering and purchasing by integrating digital solutions. The main challenges addressed were inefficient cafeteria operations and lack of security features. To address these issues, the system introduced an online platform that allows students to place orders in advance, reducing waiting times and improving security. Key security measures, such as CAPTCHA based authentication and SHA-256 encryption, were implemented to protect user data, including passwords. Functional testing by two lecturers confirmed that all 19 system modules operated as expected, ensuring a smooth and user-friendly experience. The system allowed students to easily browse the menu, place secure orders and make payments, while vendors benefited from streamlined and efficient order management. In addition, security tests using Hash cat and John the Ripper showed strong performance in SHA-256 encryption, ensuring that user data remained protected from cyber threats. In conclusion, the cafeteria system successfully improved food ordering efficiency, strengthened security, and optimized vendor operations. The integration of CAPTCHA and SHA-256 encryption further strengthens the system's reliability, making it a secure and effective solution for cafeteria management.